GOVERNMENT SPENDING PRIORITIES AND THEIR POVERTY IMPACT: A PATH ANALYSIS IN INDONESIA - Anisa Fahmi (Faculty of Economics and Business, University of Pasundan, 2026)
This study examines the impact of government expenditure on poverty, focusing on spending in the economic, education, health, and social protection sectors. Using path analysis, it investigates both the direct and indirect effects of expenditure on poverty through economic growth. The results show that economic growth significantly reduces poverty, supporting the trickle-down effect. However, sectoral expenditures produce mixed outcomes. Economic expenditure promotes growth but increases poverty, indicating weak pro-poor targeting. Education expenditure significantly reduces poverty but constrains growth due to excessive salary allocations. Health expenditure negatively affects growth and has no significant impact on poverty. Social protection expenditure stimulates growth but fails to alleviate poverty because of targeting inefficiencies. Government expenditure does not automatically reduce poverty, as its effectiveness depends on expenditure composition, targeting accuracy, and institutional quality. The findings highlight the importance of well-targeted fiscal policies that simultaneously promote inclusive economic growth and sustainable poverty reduction.